2021
DOI: 10.1016/j.nutos.2021.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Allele a of the rs16147 variant of neuropeptide Y predicts early metabolic improvements after bariatric surgery with biliopancreatic diversion in morbid obese subjects

Abstract: Clinical Nutrition Open Science 36 (2021) 26e34 mUI/L vs. À1.7 ± 0.2 mUI/L; p ¼ 0.03), year two (delta: -1.1 ± 0.2 mUI/L vs. À1.8 ± 0.2 mUI/L; p ¼ 0.02), too. Conclusion:The presence of A allele of rs16147 genetic variant produces an early metabolic response secondary to weight loss after bariatric surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Follow‐up ranged from 6 months to 7 years. Weight loss was expressed as change in BMI in 11 studies, 25–34 percentage excess BMI loss (EBMIL) in one study, 35 percentage TWL in nine studies, 36–44 and excess weight loss (EWL) in 29 studies 45–73 . Patients underwent various types of bariatric procedures including RYGB, SG, and LAGB.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Follow‐up ranged from 6 months to 7 years. Weight loss was expressed as change in BMI in 11 studies, 25–34 percentage excess BMI loss (EBMIL) in one study, 35 percentage TWL in nine studies, 36–44 and excess weight loss (EWL) in 29 studies 45–73 . Patients underwent various types of bariatric procedures including RYGB, SG, and LAGB.…”
Section: Resultsmentioning
confidence: 99%
“…For numerous genes, only one or more SNPs were examined, and no significant association was found between the genetic variant and weight loss after bariatric surgery 33,36,40,42,46,47,54,58,63,67,68,73 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another interesting SNP site was identified in NPY (Neuropeptide Y), which is a six-amino-acid peptide neurotransmitter, expressed by chromaffin and noradrenergic cells. It was suggested that high NPY expression in the hypothalamus is related to the development of T2DM, IR, and obesity [ 181 ]. Probably, the rs16147 variant has altered interaction properties with transcription factor and other regulatory elements.…”
Section: Genetic Determinants Of the Nafld Pathogenesismentioning
confidence: 99%